2020
DOI: 10.3389/fimmu.2020.535147
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Barrier Integrity Is Disrupted In Vitro by Heme and by Serum From Sickle Cell Disease Patients

Abstract: Free extracellular heme has been shown to activate several compartments of innate immunity, acting as a danger-associated molecular pattern (DAMP) in hemolytic diseases. Although localized endothelial barrier (EB) disruption is an important part of inflammation that allows circulating leukocytes to reach inflamed tissues, non-localized/deregulated disruption of the EB can lead to widespread microvascular hyperpermeability and secondary tissue damage. In mouse models of sickle cell disease (SCD), EB disruption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…Endothelial cell monolayer function was measured using ECIS, an electric cell-substrate impedance sensing system (ECIS Zθ, Applied BioPhysics, Troy, NY), as previously described 74 . The system then applies weak alternating currents through the electrode array and continuously measures the ability of the cell monolayer to impede the movement of electrons between adjacent endothelial cells (resistance).…”
Section: Ex Vivo Evaluation Of Endothelial Cell Monolayer Functionmentioning
confidence: 99%
“…Endothelial cell monolayer function was measured using ECIS, an electric cell-substrate impedance sensing system (ECIS Zθ, Applied BioPhysics, Troy, NY), as previously described 74 . The system then applies weak alternating currents through the electrode array and continuously measures the ability of the cell monolayer to impede the movement of electrons between adjacent endothelial cells (resistance).…”
Section: Ex Vivo Evaluation Of Endothelial Cell Monolayer Functionmentioning
confidence: 99%
“…Several studies have implicated endothelial barrier disruption in the pathophysiology of sickle cell disease complications such as acute chest syndrome [37,38]. Evidence supports various molecules being released or generated by hemolysis (such as free hemoglobin, heme, and hemin) as possible mediators of this disruption [39][40][41][42]. While the plasma of our patients must contain these agents, we previously showed that the concentrations in our EV preparations were too low to affect our endothelial cells [32].…”
Section: Discussionmentioning
confidence: 79%
“…Sickle cell disease is characterized by episodes of increased hemolysis, which elevates levels of free hemoglobin and heme in the blood. 32 Challenging sickle mice with extracellular hemin, the oxidized form of heme, triggers acute chest syndrome, a pulmonary complication of SCD characterized by increased permeability of the lung vasculature. 33 We investigated whether simulating a hemolytic crisis by challenging siSOD2 hPMVECs with hemin would exacerbate differences in permeability.…”
Section: Resultsmentioning
confidence: 99%